2019
DOI: 10.7816/nesne-07-14-04
|View full text |Cite
|
Sign up to set email alerts
|

Self-Esteem, Perceived Parental Acceptance-Rejection and Parenting Styles of Adolescents with Substance Use Disroder: A Comparitive Study

Abstract: Öz Bu çalışmanın amacı madde kullanım bozukluğu olan ve olmayan genç yetişkinleri benlik saygıları ve yetiştikleri aile ortamları açısından karşılaştırmaktır. Anne ve babadan algılanan kabul-ret ve çocuk yetiştirme stilleri açısından ayırt edici faktörlerin neler olduğunun bulunması amaçlanmıştır. Araştırmanın örneklemi, Ankara Alkol ve Madde Bağımlılığı Tedavi ve Eğitim Merkezi (AMATEM) Kliniğinde yatarak ve ayakta tedavi gören, yaşları 15-25 arasında değişen (Ort. = 20.9) 140 (129'u erkek, 11'i kadın) madde … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In studies on illicit substance use in Turkey, it is reported that the male/female ratio in inpatient treatment is higher than in European Union countries. While the age range was mainly between 20-29 years (31.95 ± 11.42,) (26.09±7.87), the rate for men was recorded in several research as 92.1%, 94.07%, 94.5%, 95.67%, and 95.7% [5,[8][9][10][11][12]. It is reported that treatment applications are low due to patients' belief that cannabis is not addictive and therefore does not need to be treated.…”
Section: Situation In Turkeymentioning
confidence: 95%
See 2 more Smart Citations
“…In studies on illicit substance use in Turkey, it is reported that the male/female ratio in inpatient treatment is higher than in European Union countries. While the age range was mainly between 20-29 years (31.95 ± 11.42,) (26.09±7.87), the rate for men was recorded in several research as 92.1%, 94.07%, 94.5%, 95.67%, and 95.7% [5,[8][9][10][11][12]. It is reported that treatment applications are low due to patients' belief that cannabis is not addictive and therefore does not need to be treated.…”
Section: Situation In Turkeymentioning
confidence: 95%
“…In the study in which 76 cases treated in Ankara AMATEM were analyzed, the majority of the cases were young, single, male adults addicted to heroin. The average age of drug addicts was lower than that of alcohol addicts, and they thought that the number of treatment clinics was low, the duration of treatment was short and the treatment methods were inadequate [5,[8][9][10][11][12]. Anxiety disorders were the most common axis I diagnosis (n = 58, 22.5%) and antisocial personality disorder (n=30, 11.6%) among patients hospitalized in the Alcohol and Substance Use Disorders Treatment Center (AMATEM) of a regional hospital, according to a study assessing the sociodemographic and clinical characteristics of those patients [8].…”
Section: Situation In Turkeymentioning
confidence: 99%
See 1 more Smart Citation